1. b= -4
2. x=2/12
3. Бесконечное множество корней
4. a=2
5. n= -2,5
6. d=⅔
7. n=0
8. c=2
Пошаговое объяснение:
1. (9-2b)-(b+5)=16
9-2b-b-5=16
-3b=16+5-9
-3b=12
b= -4
2. -6x+2(5-3x)=8
-6x+10-6x=8
-12x=-2
x=2/12
3. 4(-2z+5)=14-2(4z-3)
-8z+20=14-8z+6
-8z+8z=20-20
0z=0 => бесконечное множество корней
4. 12a-1=-a+25
12a+a=25+1
13a=26
a=2
5. 4n=-2+6n+7
4n-6n=7-2
-2n=5
n=-2,5
6. -3d-10=3d-6
-3d-3d=10-6
-6d=4
d=4/6=⅔
7.-2n=5,6n
-2n-5,6n=0
-7,6n=0
n=0
8. 3(-5+c)-2(c-4)=2-7(c-1)
-15+3c-2c+8=2-7c+7
3c-2c+7c=2+7-8+15
8c=16
c=2
1.
(9-2b)-(b+5)=16
9 - 2b - b - 5 = 16
-3b + 4 = 16
3b = 4 - 16
3b = -12
b = -12 : 3
b = -4
2.
-6x+2(5-3x)=8
-6x + 10 - 6x = 8
-12x + 10 = 8
12x = 10 - 8
12x = 2
x = 2 : 12
x = 1/6
3.
4(-2z+5)=14-2(4z-3)
-8z + 20 = 14 - 8z + 6
-8z + 20 = 20 - 8z
8z - 8z = 20 - 20
0 = 0
z є (-∞ ; ∞)
уравнение имен множество корней
4.
12a-1=-a+25
12a + a = 25 + 1
13a = 26
a = 26 : 13
a = 2
5.
4n=-2+6n+7
4n = 5 + 6n
6n - 4n = -5
2n = -5
n = -5 : 2
n = -2,5
6.
-3d-10=3d-6
-3d - 3d = 10 - 6
-6d = 4
d = 4 : 6
d = 2/3
7.
-2n=5,6n
-2n - 5,6n = 0
-7,6n = 0
n = 0
8.
3(-5+c)-2(c-4)=2-7(c-1)
-15 + 3c - 2c + 8 = 2 - 7c + 7
-7 + c = 9 - 7c
c + 7c = 9 + 7
8c = 16
c = 16 : 8
c = 2
1. b= -4
2. x=2/12
3. Бесконечное множество корней
4. a=2
5. n= -2,5
6. d=⅔
7. n=0
8. c=2
Пошаговое объяснение:
1. (9-2b)-(b+5)=16
9-2b-b-5=16
-3b=16+5-9
-3b=12
b= -4
2. -6x+2(5-3x)=8
-6x+10-6x=8
-12x=-2
x=2/12
3. 4(-2z+5)=14-2(4z-3)
-8z+20=14-8z+6
-8z+8z=20-20
0z=0 => бесконечное множество корней
4. 12a-1=-a+25
12a+a=25+1
13a=26
a=2
5. 4n=-2+6n+7
4n-6n=7-2
-2n=5
n=-2,5
6. -3d-10=3d-6
-3d-3d=10-6
-6d=4
d=4/6=⅔
7.-2n=5,6n
-2n-5,6n=0
-7,6n=0
n=0
8. 3(-5+c)-2(c-4)=2-7(c-1)
-15+3c-2c+8=2-7c+7
3c-2c+7c=2+7-8+15
8c=16
c=2
Пошаговое объяснение:
1.
(9-2b)-(b+5)=16
9 - 2b - b - 5 = 16
-3b + 4 = 16
3b = 4 - 16
3b = -12
b = -12 : 3
b = -4
2.
-6x+2(5-3x)=8
-6x + 10 - 6x = 8
-12x + 10 = 8
12x = 10 - 8
12x = 2
x = 2 : 12
x = 1/6
3.
4(-2z+5)=14-2(4z-3)
-8z + 20 = 14 - 8z + 6
-8z + 20 = 20 - 8z
8z - 8z = 20 - 20
0 = 0
z є (-∞ ; ∞)
уравнение имен множество корней
4.
12a-1=-a+25
12a + a = 25 + 1
13a = 26
a = 26 : 13
a = 2
5.
4n=-2+6n+7
4n = 5 + 6n
6n - 4n = -5
2n = -5
n = -5 : 2
n = -2,5
6.
-3d-10=3d-6
-3d - 3d = 10 - 6
-6d = 4
d = 4 : 6
d = 2/3
7.
-2n=5,6n
-2n - 5,6n = 0
-7,6n = 0
n = 0
8.
3(-5+c)-2(c-4)=2-7(c-1)
-15 + 3c - 2c + 8 = 2 - 7c + 7
-7 + c = 9 - 7c
c + 7c = 9 + 7
8c = 16
c = 16 : 8
c = 2